2007
DOI: 10.1002/ptr.2347
|View full text |Cite
|
Sign up to set email alerts
|

Validation of therapeutic claims of Tinospora cordifolia: a review

Abstract: This review article attempts to correlate Ayurvedic pharmacology and therapeutic claims for Tinospora cordifolia (Tc) with the evidence generated using scientific research methodology. In the present paper, a brief description of Ayurvedic pharmacology of the plant is presented. The work carried out by researchers using extracts of Tc in various areas such as diabetes, liver damage, free radical mediated injury, infections, stress and cancer have been reviewed. Also discussed are the immunomodulatory, diuretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 57 publications
1
97
0
2
Order By: Relevance
“…The preliminary phytochemical analysis showed that T. cordifolia contains saponins, tannins, terpenoids, flavonoids, alkaloids and glycosides, which conformed with descriptions of the plant's phytochemical constituents as described in the literature [1]. The purpose of the toxicity study was to evaluate whether the plant extract was toxic in nature or not.…”
Section: T Cordifolia Phytochemical Analysis and Toxicity Studiessupporting
confidence: 63%
“…The preliminary phytochemical analysis showed that T. cordifolia contains saponins, tannins, terpenoids, flavonoids, alkaloids and glycosides, which conformed with descriptions of the plant's phytochemical constituents as described in the literature [1]. The purpose of the toxicity study was to evaluate whether the plant extract was toxic in nature or not.…”
Section: T Cordifolia Phytochemical Analysis and Toxicity Studiessupporting
confidence: 63%
“…Gastric irritation is a common side effect of NSAIDs while Tinospora possesses gastro protective activity [2] which is a beneficial property while using it as an analgesic.…”
Section: Test Drugs and Chemicalsmentioning
confidence: 99%
“…It is found almost everywhere in India and in Himalayas, even up to 1000 feet height. Its habitat ranges across a wide region in India spreading from Kumaon Mountains to Kanyakumari [2]. It is also found in China, Myanmar, Sri Lanka, Thailand, Philippines, Indonesia, Malaysia, Borneo, Vietnam, Bangladesh, North Africa, West Africa and South Africa [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…have been known for stimulating and targeting APCs to up-regulate Thl responses and used as vaccine adjuvants either mixed with or conjugated to immunogen. Picrosides 6 isolated from Picrorhiza kurroa, Cardioside 7isolated from Tinospora cordifolia possesses potential immunostimulatory activity (Panchabhai, Kulkarni et al 2008). Cannabidiol 8 and tetrahydrocannabinol 9 isolated from Cannbis sativa significantly attenuated the elevation of IL-2, IL-4, IL-5, and IL-13 and represent the potential therapeutic utility.…”
Section: Plant Based Products Currently Under Investigationmentioning
confidence: 99%